Kekuatan Geser Balok Pada Kapasitas Ultimate Balok Tersusun Kayu – Plywood - Eddy Purwanto (UNIVERSITAS LAMPUNG, 2012)
The use of plywood as a construction material to hold the load as the beam has not been widelyused. It is due to little data and information in a plywood timber strength especially against theshear bearing. The research was conducted to determine the strength of the beam composed ofplywood (meranti wood origin) using adhesives Urea Formaldehyde (UF) for shear strength.From the test results show the use of the number of layers of plywood on the beam web's influenceon forces arrayed logs. Average strength achieved in block structured web thickness of 5 cm at2498 kg, 10 cm thick web of 4649 kg and a 15 cm thick web of 4443 Kg.